Pengaruh Penggunaan QRIS terhadap Peningkatan Pendapatan dengan Pemanfaatan E-Wallet sebagai Variabel Mediasi: Studi Kasus pada UMKM di Kabupaten Semarang - Nisa Amalia Maulida Hanifah; Fajar Suryatama; M.Arif Rakhman (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of QRIS usage on the increase in MSME income with the utilization of e-wallets as a mediating variable in the Semarang Regency area. The research method used is a quantitative associative approach, with data collected through questionnaires distributed to 30 MSME actors who have used QRIS, and analyzed using SmartPLS 4.0 software. The results show that the use of QRIS does not have a significant effect on increasing MSME income. However, QRIS usage has a positive and significant effect on the utilization of e-wallets. Meanwhile, the utilization of e-wallets does not have a significant effect on increasing MSME income and is also unable to mediate the relationship between QRIS usage and income growth. These findings indicate that although digital payment systems provide convenience and efficiency in transactions, their utilization has not been fully optimized in increasing MSME income. Therefore, improving digital literacy and optimizing the use of digital payment technology features are necessary to maximize the economic benefits for MSMEs.